Energy savings potential by substituting driving with walking and cycling for short distance - Mahlia, Teuku Meurah Indra; Husnawan, M.; Masjuki, Haji Hassan; Remuslara, L.; Saidur, Rahman (2008)
Vehicles energy consumption produces several emissions such as carbon dioxide (CO2), nitrogen oxide (NOx) and noise. This paper attempts to evaluate potential reduction in oil consumption and CO2 emissions if the obese and overweight conditions were eliminated from the adult population through the use of walking or cycling for transportation, and if individuals between the ages of 10 and 64 adopted recommended levels of daily exercise by walking or cycling instead of driving. Substantial co-benefits accompany widespread adoption of physical activity. The results found that the reductions in emissions from substituting driving with walking and cycling are significant enough to show a possible improvement of air quality. The highest reduction of CO2 emissions comes from the substitution of driving with exercising by cycling for 7 hours a week, which amounts to 2.38 Tg (Teragram) of reduction.